Residual shear strength of reinforced concrete slender beams without transverse reinforcement after elevated temperatures. (15th June 2021) - Ahmad, Subhan; Bhargava, Pradeep; Chourasia, Ajay; Ju, Minkwan
Highlights: Residual shear behaviour of RC beams exposed to elevated temperatures is investigated. Shear transfer mechanism changed for the beams exposed to temperatures higher than 550 °C. A model for the computation of residual shear strength of RC beams is proposed. Abstract: Forty-eight reinforced concrete (RC) beams without transverse reinforcement were tested at ambient and after exposure to high temperatures. Beams were heated to high steady-state temperatures of 350 °C, 550 °C, and 750 °C in a programmable closed electric furnace and loaded to failure after cooling down. In addition to exposure temperature, tension reinforcement percentage (ρ) and shear-span-to-depth ratio (a/d) were kept as the variables. In the beams tested at ambient and after the elevated temperature of 350 °C, beam action was dominant, and diagonal tension failure was the observed mode of failure. When beams were exposed to 550 °C and 750 °C, beam action almost vanished, and the beams failed due to the failure of a compression strut joining the loading point and the support. After exposure to high temperatures, shear strength loss observed in beams with a lower tension reinforcement ratio was found to be more significant. Whereas, change in a/d ratio had an insignificant influence on the shear strength loss of the beams. An increase in temperature resulted in the decrease of the beams stiffness and increased the deflection corresponding to the ultimate load. An empirical model was also developed from the data of the present study for the prediction of shear strength of RC slender beams exposed to high temperatures.